Induced pluripotent stem cell-based therapies for organ fibrosis - Cheng, Wei; Fan, Chengming; Song, Qing; Chen, Ping; Peng, Hong; Lin, Ling; Liu, Cong; Wang, Bin; Zhou, Zijing (Frontiers in Bioengineering and Biotechnology, 2023)
Fibrotic diseases result in organ remodelling and dysfunctional failure and account for one-third of all deaths worldwide. There are no ideal treatments that can halt or reverse progressive organ fibrosis, moreover, organ transplantation is complicated by problems with a limited supply of donor organs and graft rejection. The development of new approaches, especially induced pluripotent stem cell (iPSC)-based therapy, is becoming a hot topic due to their ability to self-renew and differentiate into different cell types that may replace the fibrotic organs. In the past decade, studies have differentiated iPSCs into fibrosis-relevant cell types which were demonstrated to have anti-fibrotic effects that may have the potential to inform new effective precision treatments for organ-specific fibrosis. In this review, we summarize the potential of iPSC-based cellular approaches as therapeutic avenues for treating organ fibrosis, the advantages and disadvantages of iPSCs compared with other types of stem cell-based therapies, as well as the challenges and future outlook in this field.